Peramalan Kedatangan Wisatawan Mancanegara Ke Indonesia Menurut Kebangsaan Perbulannya Menggunakan Metode Multilayer Perceptron - Harun Mukhtar; Muhammad Rifaldo; Reny Medikawati Taufiq; Yoze Rizki (Jurnal CoSciTech (Computer Science and Information Technology), 2021)
The beauty of tourist attractions in Indonesia has a certain attraction for foreign tourists to serve as a place for vacation. However, the number of visitors needs to be predicted to anticipate an increase or decrease in the number of visitors, so that the state can determine policies regarding changes in the number of visitors in the future. Forecasting is used to predict previous data patterns so that further data patterns can be known. Multilayer Perceptron (MLP) is a neural network development that can be used for modeling time series data. Several researchers have conducted research using the Multilayer Perceptron method in making predictions. Forecasting systems or forecasting are very helpful in the current era, forecasting aims to predict future conditions. Prediction results, obtained 82% accuracy for tourist predictions in Period 7, namely September 2020, 97% for Prediction Period 8, namely December 2020 so that the Number of Tourists for Period 9 is 7,106 people.